2013
DOI: 10.1142/s1758825113500191
|View full text |Cite
|
Sign up to set email alerts
|

Periodic and Chaotic Responses of an Axially Accelerating Viscoelastic Beam Under Two-Frequency Excitations

Abstract: This study focuses on the steady-state periodic response and the chaotic behavior in the transverse motion of an axially moving viscoelastic tensioned beam with two-frequency excitations. The two-frequency excitations come from the external harmonic excitation and the parametric excitation from harmonic fluctuations of the moving speed. A dynamic model is established to include the finite axial support rigidity, the material derivative in the viscoelastic constitution relation, and the longitudinally varying t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 47 publications
(56 reference statements)
0
9
0
Order By: Relevance
“…The transverse vibration of the traveling beam with the external harmonic excitation is governed Fig. 1 Traveling beam with simply supported ends by [23] ρA(u, tt +γu,…”
Section: Mathematical Modelmentioning
confidence: 99%
“…The transverse vibration of the traveling beam with the external harmonic excitation is governed Fig. 1 Traveling beam with simply supported ends by [23] ρA(u, tt +γu,…”
Section: Mathematical Modelmentioning
confidence: 99%
“…[26,27] have discovered rich nonlinear phenomena, as well as Awrejcewicz et al have shown that continuous mechanical systems may possess various bifurcations, different types of chaos, quasi-periodic orbits [47,48], the nonlinear dynamics of the pulleyÀbelt system with one-way clutch under two-excitation should be an interesting further research direction.…”
Section: Discussionmentioning
confidence: 99%
“…By the extension of Hamilton's principle, Behdinan et al [1997] obtained the governing equations for flexible sliding beams with a constant velocity deployed or retrieved through a rigid channel based on the assumptions of Euler-Bernoulli beam theory. Many researchers applied directly extended Hamilton's principle to study the nonlinear vibration of axially moving beams and plates with simple geometric conditions such as Ghayesh and Farokhi [2015], Tang et al [2008], Seddighi and Eipakchi [2016], Ding and Zu [2013], Ali and Elham [2017]. Based on the extended Hamilton principle, Zhang et al obtained many remarkable results for the nonliner vibration of the axially moving beam or plate [Cao and Zhang, 2006, Chen et al, 2007, Chen et al, 2010, Yao et al, 2012, Yang et al, 2012, Yang and Zhang, 2014 But, these works did not point out clearly what description has been used.…”
Section: Introductionmentioning
confidence: 99%